PHAs from industrial waste by applying the threestep process - Rangel, Catarina Sofia Cirne (2018)
Currently one of the greatest concerns worldwide focuses on the development of new sustainable materials that can be used to replace petroleum-based products. For this reason, the study of the production of bioplastics has been subjected to considerable research in order to achieve process optimization and production costs reduction. In this context, the study of the production of polyhydroxyalkanoate (PHA) by mixed microbial cultures (MMC) is worthwhile. In this work, the three-step process was tested for PHA production. In a first step, a feedstock of the paper industry, hardwood sulphite spent liquor (HSSL) was submitted to acidogenic fermentation in order to produce a mixture rich in volatile fatty acids (VFAs), which was used as substrate in the next two steps. In the second step, a MMC collected from a wastewater treatment plant (WWTP) was submitted to Aerobic Dynamic Feeding (ADF) conditions in a Sequencing Batch Reactor (SBR) in order to select PHA-accumulating organisms. A pseudo-stationary state was reached after 60 days of SBR operation. In the third step, the ability of the selected MMC to accumulate PHA was tested. The selected MMC reached a maximum PHA content of 47.1%. The bacterial community was analysed through fluorescence in situ hybridization (FISH). Bacteria belonging to the four main classes were identified: Beta- (44.7 ± 2.7%), Alpha- (13.6 ± 1.3%) and Gammaproteobacteria (2.40 ± 1.1%) and Bacteroidetes (9.20 ± 3.8%). Regarding the genus level, inside the Betaproteobacteria, a considerable amount of Acidovorax (25.9 ± 3.1%) was found and only small amounts of Thauera (0.72 ± 0.25%) and Azoarcus (0.62 ± 0.02%) were detected. Defluvicoccus related to Tetrad Forming Organisms (0.75 ± 0.53%) belonging to Alphaproteobacteria was detected in small amount. A clone library was prepared and several clones were identified as organisms already described as PHA-producers.